Digital Literacy, Environment, and E-Commerce Use Toward Digital Entrepreneurial Intentions via Social Media among Generation Z Students - Isma, Andika; Hajar Dewantara; Andi Naila Quin Azisah Alisyahbana; Salim Diarra (Quantitative Economics and Management Studies, 2025)
The rapid development of digital technology is reshaping entrepreneurial landscapes, particularly among Generation Z students who are highly engaged with digital platforms. This study investigates the influence of digital literacy, environmental factors, and e-commerce usage on digital entrepreneurial intentions, with social media serving as a mediating variable. A quantitative descriptive-explanatory approach was employed, involving 105 Generation Z student respondents selected through proportional random sampling. The findings reveal that digital literacy, environment, and e-commerce use have a significant impact on digital entrepreneurial intentions, both directly and indirectly through social media. Social media enhances the connection between these factors and entrepreneurial intentions by providing a platform for idea sharing, business promotion, and networking. These insights highlight the importance of integrating digital competencies and social media utilization into entrepreneurship education to cultivate innovative and digitally empowered young entrepreneurs.